Numerical model for prediction of wrinkling behavior on a thin-membrane structure - Shoko ARITA (The Japan Society of Mechanical Engineers, 2014)
One of the key aspects of developing gossamer space structures is the prediction of wrinkles and slacks in the material. Wrinkles, which essentially refer to elastic buckling, have been analyzed numerically using finite element methods (FEMs) with shell elements, but at a high computational cost. Therefore, membrane elements, which ignore bending stiffness and consider only in-plane stress, have been employed to reduce the computational cost. However, the compressive stiffness of the membrane cannot be ignored when predicting wrinkle regions precisely in membrane structures. Some previous studies have employed membrane elements considering small, constant non-zero values of compressive stiffness; these membrane elements can predict the distribution of principal stress as the wrinkle regions. However, none of these traditional methods can determine the value of compressive stiffness, and some parts of the principal stress distribution in slack areas do not correspond to the actual phenomenon. Therefore, in order to determine compressive stiffness logically and uniquely, we propose a new numerical calculation model, the modified-stiffness reduction model (Mod-SRM), which is based on the stretchable elastic theory. Moreover, by comparison with the other FEM models, we confirm that Mod-SRM represents the slack region more accurately than the traditional models.